Turbulence forced convection heat transfer over double forward facing step flow - Yilmaz, Ilker; Öztop, Hakan Fehmi (My University, 2006)
Turbulent forced heat transfer for double forward facing step flow was studied numerically. The bottom wall of the channel is heated at uniform temperature and the flow temperature at the upstream is colder than the wall. Two adiabatic steps are located together with different lengths and heights. The solutions are done using commercial code FLUENT which uses finite volume method. The standard k - ? turbulence model is employed to obtain turbulence flow modeling for double forward step. Effects of step heights, step lengths and Reynolds numbers on heat transfer and fluid flow are investigated as main parameters. Results showed that the second step can be use as a control device for both heat transfer and fluid flow. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Double forward facing step; Forced convection; Turbulence